NFPP / C-nvp / c hollow porous spherical composite nanoparticles, and preparation method and application thereof
Patent Information
- Application Number
- CN202611030525.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-11
- Publication Date
- 2026-10-23
AI Technical Summary
[0010]目前对NFPP的改性研究尚处于起步阶段,还有很多技术瓶颈和核心科学问题亟待解决:1)电子导电性较低,导致充放电过程中电子传输缓慢,影响倍率性能和能量效率;2)材料中的Na+离子扩散速率较慢,限制了充放电速度,尤其在快速充放电时表现不佳,第二个Na+脱/嵌的容量需深度开发;3)橄榄石结构NaFePO4虽可以通过传统的物理途径获得,但晶体中缺乏Na+迁移通道导致缺失电化学活性,在充放电过程中,材料可能发生相变或体积变化,导致结构不稳定,影响循环寿命;4)NFPP对合成温度敏感,合成过程中难以精确控制成分和结构,相关单相到复合相的研究机理尚未涉及
本发明通过原位碳包覆与NFPP/C、NVP/C两相掺杂协同提高电子电导率,降低电极极化,从而提升了材料的导电性,并且通过NASICON结构与异质界面加速Na+传输,提升倍率性能,从而优化了材料的动力学,进而解决了NFPP材料电子导电性差、钠离子扩散动力学缓慢的技术问题。
Smart Images

Figure CN122968265A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery electrode material technology, specifically relating to an NFPP / C-NVP / C hollow porous spherical composite nanoparticle, its preparation method, and its application. Background Technology
[0002] Sodium is abundant in the Earth's crust (abundance 2.32%), and sodium-ion batteries (SIBs) are considered a promising large-scale energy storage alternative to conventional lithium-ion batteries (LIBs) due to their competitive advantages such as abundant resources, low cost, and environmental friendliness. However, the differences between Na and Li bring some fundamental problems hindering the practical application of sodium-ion batteries. In particular, Na... + The size of (1.02 Å) is much larger than that of Li. + The diffusion kinetics (0.69 Å) result in slow diffusion dynamics and reduced power output. Therefore, improving the diffusion dynamics of sodium-ion batteries is necessary to increase power density and facilitate wider application.
[0003] In the 1980s, M.B. Armond et al. first proposed the concept of the "rocking chair battery," in which both the positive and negative electrodes use intercalation compounds, laying the theoretical foundation for alkali metal secondary batteries. In 1980, J.B. Goodenough et al. discovered the excellent lithium insertion / extraction performance of layered lithium cobalt oxide (LiCoO2), propelling the commercialization of lithium-ion batteries. Based on this research, P. Hagenmuller et al. synthesized layered sodium cobalt oxide (NaxCoO2) in the same year and initially revealed the relationship between the material's structure and its sodium storage performance.
[0004] See Figure 1 As shown, the core components of a sodium-ion battery include: a positive electrode, a negative electrode, an electrolyte, and a separator. Other minor components include current collectors, additives such as conductive agents, and binders. The positive electrode material, in particular, plays a crucial role in both performance and cost. Therefore, it is necessary to research and develop high-voltage positive electrode materials with good rate performance to improve the energy density and power density of sodium-ion batteries.
[0005] Taking a sodium-ion battery composed of a layered oxide NaMO2 positive electrode and a hard carbon C negative electrode as an example, its working principle is as follows: During charging, NaMO2 releases sodium ions into the electrolyte. Under the influence of an electric field, the sodium ions migrate through the separator towards the negative electrode side; electrons are transferred to the negative electrode through the external circuit and enter the hard carbon negative electrode with the sodium ions that have migrated in the electrolyte, maintaining the material's electroneutrality. After charging, NaMO2 gradually loses sodium ions and transforms into a sodium-depleted phase, Na. 1-x MO2; correspondingly, C transforms into the sodium-rich phase Na due to the continuous accommodation of sodium ions. x C. After discharge, the positive and negative electrodes revert to the original NaMO2 and C phases, respectively.
[0006] Currently, active materials store sodium ions mainly through three mechanisms: intercalation / deintercalation reaction, alloying reaction, and conversion reaction. If classified according to the sodium storage mechanism of active materials, almost all cathode materials reported in existing literature follow the intercalation / deintercalation reaction mechanism, including: transition metal oxides (such as NaCoO2, NaMnO2, etc.), polyanionic compounds (such as NaFePO4, Na3V2(PO4)3, Na2FePO4F, etc.), and Prussian blue materials (such as Na4Fe(CN)6, Na2MnFe(CN)6, etc.).
[0007] Based on the current research status, the actual specific capacity obtained by cathode materials (80~150mAh / g) is still far lower than that of anode materials (carbon materials: 200~250mAh / g; alloy materials: 400~600mAh / g). Therefore, focusing on the research and development of high-performance sodium-intercalated cathode materials is the key to improving the energy / power density of sodium-ion batteries, and its breakthrough significance for energy storage sodium-ion battery technology is significant.
[0008] Currently, the most studied cathode materials include layered and spinel-structured transition metal oxides, NASICON-type network compounds, phosphates, and pyrophosphates. Among these, layered oxides suffer from poor process stability and high environmental requirements due to their inherent structure, while Prussian blue materials are prone to crystallization. Na4Fe3(PO4)2P2O7 (NFPP), with its high theoretical capacity, outstanding low-temperature performance, good thermal stability, and convenient preparation process, has become one of the most promising cathode materials.
[0009] NFPP can be considered a complex: Na4Fe3(PO4)2P2O7 = 2“NaFePO4” + “Na2FeP2O7”. First, NaFePO4 is a wide-bandgap insulator, and its low electronic conductivity severely affects its electrochemical performance. Pure NaFePO4 exhibits poor electrochemical performance. Second, in the Na2FeP2O7 crystal, the P2O7 group has a larger open framework, a more stable structure, and is easier to synthesize. However, due to the high molecular weight of the pyrophosphate group, only a relatively low capacity can be obtained. Therefore, improving the electronic conductivity and specific capacity of the material is key to improving its electrochemical performance.
[0010] Current research on the modification of NFPP is still in its early stages, and many technical bottlenecks and core scientific issues remain to be addressed: 1) Low electronic conductivity leads to slow electron transport during charging and discharging, affecting rate performance and energy efficiency; 2) Na in the material... + The slow ion diffusion rate limits the charge / discharge speed, especially its poor performance during rapid charge / discharge. The second Na... +The capacity for insertion / extraction needs further development; 3) Although olivine-structured NaFePO4 can be obtained through traditional physical methods, the crystal lacks Na. + Migration channels lead to a lack of electrochemical activity. During charge and discharge, the material may undergo phase transitions or volume changes, resulting in structural instability and affecting cycle life. 4) NFPP is sensitive to synthesis temperature, making it difficult to precisely control composition and structure during synthesis. The research mechanism of the related single-phase to composite phase transformation has not yet been explored. Therefore, a systematic study of the above problems is needed, and new methods should be sought to modify NFPP. Summary of the Invention
[0011] To address the problems existing in the prior art, this invention provides NFPP / C-NVP / C hollow porous spherical composite nanoparticles, their preparation method, and applications. By constructing carbon coating and NVP (Na3V2(PO4)3) doping to modify NFPP (Na4Fe3(PO4)2P2O7), the electrochemical performance of the material is significantly improved based on the realization of two-phase in-situ composite and in-situ carbon coating.
[0012] To solve the above-mentioned technical problems and achieve the above-mentioned technical effects, the present invention is implemented through the following technical solution: A method for preparing NFPP / C-NVP / C hollow porous spherical composite nanoparticles includes the following steps: Step 1: Prepare NFPP / C (Na4Fe3(PO4)2P2O7 / C) hollow porous spherical nanoparticle precursor; First, sodium source, iron source, and phosphorus source are placed in a solvent in proportion, and carbon source is added. The mixture is stirred until a transparent and uniform first mixed slurry (solid content of 20-50%) is formed. Then, the first mixed slurry is sand-milled and spray-dried to obtain a dried NFPP / C hollow porous spherical nanoparticle precursor. Step 2: Prepare NVP / C (Na3V2(PO4)3 / C) hollow porous spherical nanoparticle precursors; First, sodium source, vanadium source, and phosphorus source are placed in a solvent in proportion, and phosphate chelating agent and carbon source are added. The mixture is stirred until a transparent and uniform second mixed slurry (solid content of 20-50%) is formed. Then, the second mixed slurry is sand-milled and spray-dried to obtain a dried NVP / C hollow porous spherical nanoparticle precursor. Step 3: Prepare NFPP / C-NVP / C hollow porous spherical composite nanoparticles; The NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed in a certain mass ratio and then calcined in a non-oxidizing atmosphere for a certain time to finally obtain two composites with carbon-coated NFPP hollow porous spherical nanoparticles and NVP hollow porous spherical nanoparticles, namely NFPP / C-NVP / C hollow porous spherical composite nanoparticles.
[0013] Furthermore, in step 1, the molar ratio of the sodium source, the iron source, and the phosphorus source is Na:Fe:P = 4:3:4, wherein the sodium source is introduced through sodium acetate trihydrate, the iron source is introduced through ferric phosphate, and the phosphorus source is introduced through one of ferric phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid.
[0014] Furthermore, in step 2, the molar ratio of the sodium source, the vanadium source, and the phosphorus source is Na:V:P=3:2:3, wherein the sodium source is introduced by sodium dihydrogen phosphate dihydrate, the vanadium source is introduced by ammonium metavanadate, the phosphorus source is introduced by sodium dihydrogen phosphate dihydrate, and the phosphoric acid chelating agent is one of oxalic acid and citric acid.
[0015] Furthermore, in steps 1 and 2, the carbon source is introduced through one of sucrose, soluble starch, cellulose, glucose, ascorbic acid, and citric acid; the total amount of the carbon source added is 1 to 10% of the total mass of the sodium source, the iron source, the phosphorus source, and the vanadium source.
[0016] Furthermore, in steps 1 and 2, the solvent is one of ethanol, acetic acid, or deionized water, and the amount added is 200 mL.
[0017] Furthermore, in steps 1 and 2, the sanding method is as follows: First, pour the first mixed slurry and the second mixed slurry into their respective sand mills and stir for 1-2 hours; The mixture is then subjected to coarse and fine grinding for 3 to 10 hours to ensure that the particle size of the raw materials in the first and second mixed slurries is uniformly controlled between 0.4 ± 0.1 μm.
[0018] Furthermore, in steps 1 and 2, the spraying method is as follows: The first and second mixed slurries, after sand milling, are fed to corresponding spray dryers at a feeding rate of 200 mL / h. The inlet temperature of the spray dryer is 200°C and the outlet temperature is 100°C, thereby obtaining the dried NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor, respectively.
[0019] Furthermore, in step 3, the calcination method is as follows: First, the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed at a mass ratio of 5:5, 6:4 or 7:3, and placed in a tube furnace. Under the atmosphere of argon or argon-hydrogen mixed gas, the mixture is pre-calcined at 300~400℃ (preferably 300℃) for 1~4h (preferably 3h) at a heating rate of 2℃ / min, and then calcined at 500~750℃ (preferably 500℃) for 5~15h (preferably 15h). During the calcination process, the sodium source, the iron source, and the phosphorus source in the NFPP / C hollow porous spherical nanoparticle precursor react to generate Na4Fe3(PO4)2P2O7+NH3, which is the composite sodium iron pyrophosphate NFPP; the sodium source, the vanadium source, the phosphorus source, and the phosphate chelating agent in the NVP / C hollow porous spherical nanoparticle precursor react to generate Na3V2(PO4)3, which is the sodium vanadium phosphate NVP; Meanwhile, the carbon source in the NFPP / C hollow porous spherical nanoparticle precursor and the carbon source in the NVP / C hollow porous spherical nanoparticle precursor can first act as reducing agents to ensure that the elements in the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed uniformly, and after calcination, a dense and uniform conductive carbon layer is formed on the surface of NFPP and NVP respectively, thereby greatly improving the performance of the electrode material; Ultimately, hollow porous spherical nanoparticles are formed by in-situ composite of two phases, NFPP / C and NVP / C, and in-situ carbon coating, namely NFPP / C-NVP / C hollow porous spherical composite nanoparticles, in which NFPP / C is a mixed polyanionic phase of orthorhombic crystal system (Pnma), and NVP / C is a trigonal NASICON phase.
[0020] A hollow porous spherical composite nanoparticle of NFPP / C-NVP / C prepared by the above preparation method.
[0021] The above-prepared NFPP / C-NVP / C hollow porous spherical composite nanoparticles are used in the preparation of cathode materials for sodium-ion batteries.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention improves the electronic conductivity and reduces electrode polarization by synergistically enhancing in-situ carbon coating and two-phase doping of NFPP / C and NVP / C, thereby improving the material's conductivity. Furthermore, it accelerates the Na+ process through the NASICON structure and heterojunction. +The transmission improves rate performance, thereby optimizing the material's kinetics and solving the technical problems of poor electronic conductivity and slow sodium ion diffusion kinetics in NFPP materials.
[0023] This invention extends cycle life by buffering volume changes through a rigid polyanionic framework and hollow structure, thereby stabilizing the material structure and improving the structural stability and cycle life of NFPP materials during charge and discharge processes.
[0024] This invention broadens the voltage window through voltage platform complementarity and improves the overall energy density through capacity matching, thereby forming material performance complementarity and achieving efficient synergy between NFPP and NVP materials, optimizing voltage window and energy density.
[0025] The process of this invention is simple, the synthesis temperature is low, the energy consumption is low, it is easy to scale up, and iron-based resources are abundant. It reduces the amount of vanadium used while ensuring performance, thereby reducing material costs. Therefore, the cost is controllable and it has process advantages.
[0026] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Specific embodiments of the present invention are given in detail below with reference to the accompanying drawings. Attached Figure Description
[0027] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the structure of a sodium-ion battery in the prior art.
[0028] Figure 2 This is a schematic flowchart of the preparation method of the NFPP / C-NVP / C hollow porous spherical composite nanoparticles of the present invention.
[0029] Figure 3 This is a comparison of the appearance of the NFPP / C hollow porous spherical nanoparticle precursor before and after calcination in an embodiment of the present invention.
[0030] Figure 4 The image shows the XRD pattern of the NFPP / C hollow porous spherical nanoparticles in this embodiment of the invention.
[0031] Figure 5 This is one of the SEM images of the NFPP / C hollow porous spherical nanoparticles in the embodiments of the present invention.
[0032] Figure 6This is the second SEM image of the NFPP / C hollow porous spherical nanoparticles in this embodiment of the invention.
[0033] Figure 7 The first charge-discharge curves of NFPP / C hollow porous spherical nanoparticles at different rates are shown in the embodiments of the present invention.
[0034] Figure 8 This is a diagram showing the number of cycles of NFPP / C hollow porous spherical nanoparticles at a 0.5C / 1C ratio in an embodiment of the present invention.
[0035] Figure 9 This is a comparison of the appearance of the NVP / C hollow porous spherical nanoparticle precursor before and after calcination in an embodiment of the present invention.
[0036] Figure 10 The image shows the XRD pattern of the NVP / C hollow porous spherical nanoparticles in this embodiment of the invention.
[0037] Figure 11 This is a SEM image of the NVP / C hollow porous spherical nanoparticles in an embodiment of the present invention.
[0038] Figure 12 The first charge-discharge curves of the NVP / C hollow porous spherical nanoparticles at different rates are shown in the embodiments of the present invention.
[0039] Figure 13 This is a diagram showing the number of cycles of the NVP / C hollow porous spherical nanoparticles in this embodiment of the invention at a rate of 0.5C / 1C. Detailed Implementation
[0040] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings to provide a clearer understanding of the invention's purpose, features, and advantages. It should be understood that the embodiments shown in the drawings are not intended to limit the scope of the invention, but are merely illustrative of the essential spirit of the invention's technical solution.
[0041] In the following description, certain specific details are set forth for the purpose of illustrating various disclosed embodiments in order to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the art will recognize that embodiments may be practiced without one or more of these specific details. In other instances, well-known apparatuses, structures, and techniques associated with this application may not have been shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.
[0042] Unless the context requires otherwise, throughout the specification and claims, the word “comprising” and its variations, such as “including” and “having”, shall be understood to have an open, inclusive meaning, that is, to be interpreted as “including, but not limited to”.
[0043] Throughout this specification, references to "an embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Therefore, the appearance of "in an embodiment" or "an embodiment" in various places throughout the specification does not necessarily refer to the same embodiment. Furthermore, a particular feature, structure, or characteristic may be combined in any manner in one or more embodiments.
[0044] The singular forms “a” and “the” used in this specification and the appended claims include plural references unless otherwise expressly stated herein. It should be noted that the term “or” is generally used to mean “and / or” unless otherwise expressly stated herein.
[0045] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. Unless otherwise specified, all reagents and materials used in the present invention are commercially available.
[0046] See Figure 2 As shown, this invention first provides a method for preparing NFPP / C-NVP / C hollow porous spherical composite nanoparticles, including the following steps: Step 1: Prepare NFPP / C hollow porous spherical nanoparticle precursors; First, sodium, iron, and phosphorus sources are placed in an appropriate amount of solvent in a certain proportion, and carbon source is added. The mixture is stirred until a transparent and uniform first mixed slurry (solid content of 20-50%) is formed. Then, the first mixed slurry is sand-milled and spray-dried to obtain a dried NFPP / C hollow porous spherical nanoparticle precursor.
[0047] In this step, the molar ratio of sodium source, iron source, and phosphorus source is Na:Fe:P = 4:3:4. The sodium source is introduced through sodium acetate trihydrate, the iron source is introduced through ferric phosphate, the phosphorus source is introduced through one of ferric phosphate and ammonium dihydrogen phosphate, diammonium hydrogen phosphate, or phosphoric acid, and the carbon source is introduced through one of sucrose, soluble starch, cellulose, glucose, ascorbic acid, or citric acid. The solvent is one of ethanol, acetic acid, or deionized water, and the added volume is 200 mL.
[0048] In this step, the sand milling method is to pour the first mixed slurry into a sand mill, stir it for 1 to 2 hours, and then perform coarse grinding and fine grinding for 3 to 10 hours, so that the particle size of the raw materials in the first mixed slurry is uniformly controlled between 0.4 ± 0.1 μm.
[0049] In this step, the spraying method is to feed the first mixed slurry after sand milling at a feeding rate of 200 mL / h to a spray dryer with an inlet air temperature of 200°C and an outlet air temperature of 100°C for spraying, thereby obtaining the dried NFPP / C hollow porous spherical nanoparticle precursor.
[0050] Step 2: Prepare NVP / C hollow porous spherical nanoparticle precursors; First, sodium source, vanadium source, and phosphorus source are placed in an appropriate amount of solvent in proportion, and phosphate chelating agent and carbon source are added. The mixture is stirred until a transparent and uniform second mixed slurry (solid content of 20-50%) is formed. Then, the second mixed slurry is sand-milled and spray-dried to obtain a dried NVP / C hollow porous spherical nanoparticle precursor.
[0051] In this step, the molar ratio of sodium source, vanadium source, and phosphorus source is Na:V:P=3:2:3. The sodium source is introduced through sodium dihydrogen phosphate dihydrate, the vanadium source is introduced through ammonium metavanadate, and the phosphorus source is introduced through sodium dihydrogen phosphate dihydrate. The phosphate chelating agent is one of oxalic acid and citric acid. The carbon source is introduced through one of sucrose, soluble starch, cellulose, glucose, ascorbic acid, and citric acid. The solvent is one of ethanol, acetic acid, and deionized water, and the added volume is 200 mL.
[0052] In this step, the sand milling method is to pour the second mixed slurry into a sand mill, stir it for 1 to 2 hours, and then perform coarse grinding and fine grinding for 3 to 10 hours, so that the particle size of the raw materials in the second mixed slurry is uniformly controlled between 0.4 ± 0.1 μm.
[0053] In this step, the spraying method is to feed the second mixed slurry after sand milling at a feeding rate of 200 mL / h to a spray dryer with an inlet air temperature of 200°C and an outlet air temperature of 100°C for spraying, thereby obtaining the dried NVP / C hollow porous spherical nanoparticle precursor.
[0054] It should be noted that the total amount of carbon source added in steps 1 and 2 is 1 to 10% of the total mass of all sodium, iron, phosphorus and vanadium sources.
[0055] Step 3: Prepare NFPP / C-NVP / C hollow porous spherical composite nanoparticles; First, the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed at a certain mass ratio and placed in a tube furnace. Under non-oxidizing atmosphere, the mixture is pre-calcined at 300~400℃ for 1~4h at a heating rate of 2℃ / min, and then calcined at 500~750℃ for 5~15h.
[0056] As one embodiment, the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed at a mass ratio of 5:5, 6:4 or 7:3, preferably at a mass ratio of 6:4.
[0057] As one embodiment, a non-oxidizing atmosphere is preferably argon or an argon-hydrogen mixture.
[0058] As one embodiment, the pre-calcination temperature is preferably 300°C and the time is preferably 3 hours, and the calcination temperature is preferably 500°C and the time is preferably 15 hours.
[0059] During the calcination process, the sodium, iron, and phosphorus sources in the NFPP / C hollow porous spherical nanoparticle precursor react to generate Na4Fe3(PO4)2P2O7+NH3, which is the composite sodium iron pyrophosphate NFPP; the sodium, vanadium, phosphorus, and phosphate chelating agent in the NVP / C hollow porous spherical nanoparticle precursor react to generate Na3V2(PO4)3, which is the sodium vanadium phosphate NVP.
[0060] Taking sodium acetate trihydrate, ferric phosphate, and ammonium dihydrogen phosphate as sodium, iron, and phosphorus sources, respectively, the reaction equation for NFPP is as follows: 4CH3COONa·3H2O+3FePO4+1NH4H2PO4→Na4Fe3(PO4)2P2O7+NH3↑+3 / 4CO2↑+39 / 2H2O.
[0061] Taking ammonium metavanadate, dihydrate, and sodium dihydrogen phosphate as sodium, vanadium, and phosphorus sources, and oxalic acid as a phosphate chelating agent as an example, the reaction equation for NVP is as follows: 2NH4VO3+NaH2PO4·2H2O+2HOOCCOOH·2H2O→Na3V2(PO4)3+4CO2↑+2NH3↑+16H2O.
[0062] Meanwhile, the carbon sources in the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor can first act as reducing agents to ensure that the elements in the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed uniformly, and after calcination, a dense and uniform conductive carbon layer is formed on the surface of NFPP and NVP respectively, thereby greatly improving the performance of the electrode material.
[0063] Ultimately, hollow porous spherical nanoparticles are formed by in-situ composite of two phases, NFPP / C and NVP / C, and in-situ carbon coating, namely NFPP / C-NVP / C hollow porous spherical composite nanoparticles, in which NFPP / C is a mixed polyanionic phase of orthorhombic crystal system (Pnma), and NVP / C is a trigonal NASICON phase.
[0064] This invention utilizes X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) to analyze the crystal structure and microstructure of materials. X-ray photoelectron spectroscopy (XPS) and energy-dispersive X-ray spectroscopy (EDS) are used to determine the chemical composition of the materials. Cyclic voltammetry (CV), constant current charge-discharge testing, and electrochemical impedance spectroscopy (EIS) are used to evaluate the electrochemical performance of the materials. An electrode is prepared by mixing active materials, conductive agents, and binders in a specific ratio and coating them onto a current collector. Button cells or pouch cells are assembled in a glove box, using sodium metal as the counter electrode, and the cycle performance, rate performance, and coulombic efficiency of the cells are tested.
[0065] The researchers of this invention first prepared NFPP / C hollow porous spherical nanoparticles and NVP / C hollow porous spherical nanoparticles separately according to the above preparation method, and analyzed the composition, structure, morphology and size of the two materials, as well as evaluated their electrochemical performance.
[0066] See Figure 3 As shown, Figure 3 The yellow powder on the left is the NFPP / C hollow porous spherical nanoparticle precursor before calcination. Figure 3 The black powder on the right side is NFPP / C hollow porous spherical nanoparticles obtained after calcination. (See also...) Figure 4 As shown, XRD indicates that the target product, NFPP / C hollow porous spherical nanoparticles, is a pure phase with no obvious impurities. See also... Figure 5-8 As shown, the NFPP / C hollow porous spherical nanoparticles exhibit a porous spherical structure with primary sphere diameters on the order of tens of micrometers (10~50 μm), effectively showcasing the electrochemical performance of this type of material. See also... Figure 9 As shown, Figure 9 The green powder on the left is the NVP / C hollow porous spherical nanoparticle precursor before calcination. Figure 9 The black powder on the right side is NVP / C hollow porous spherical nanoparticles obtained after calcination. See also... Figure 10 As shown, XRD indicates that the target product, NVP / C hollow porous spherical nanoparticles, is a pure phase with no obvious impurities. See also... Figure 11-13As shown, the NVP / C hollow porous spherical nanoparticle material exhibits a hollow spherical structure. Electrochemical performance tests reveal that it remains stable at over 80% after more than 100 cycles, with a specific capacity exceeding 100 and a voltage plateau of 3.4V. This work lays a solid foundation for the study of NVP composite doping-modified NFPP.
[0067] This invention achieves a novel sodium-ion battery composite cathode material with high capacity, good safety performance, excellent rate performance, and superior cycle performance by constructing an efficient NFPP / C-NVP / C composite ratio. This material combines the advantages of both NFPP / C hollow porous spherical nanoparticles and NVP / C hollow porous spherical nanoparticles, exhibiting a high voltage platform (above 3V), high specific capacity (above 100), and good cycle performance (above 100 cycles, with a capacity retention rate of over 80%).
[0068] The NFPP / C-NVP / C hollow porous spherical composite nanoparticles prepared in this invention combine two active materials, NFPP / C and NVP / C, to form a biphase composite structure, thereby improving electrochemical performance. The NVP / C hollow porous spherical nanoparticles possess a NASICON structure, and their open three-dimensional framework facilitates rapid sodium ion migration. Furthermore, the NFPP / C hollow porous spherical nanoparticles are also polyanionic materials, and both have similar synthesis methods and crystal structures, thus facilitating their doping. This invention also employs carbon coating technology to improve the material's conductivity and reduce electrode polarization. The synergistic effect of Fe and V elements in the NFPP / C-NVP / C hollow porous spherical composite nanoparticles prepared in this invention provides a multi-electron reaction mechanism, increasing specific capacity. The PO4 and P2O7 groups enhance the structural stability of the material, improving performance under high voltage. Optimizing these technologies can further improve the material's performance and promote its application in sodium-ion batteries.
[0069] NVP belongs to the NASICON-type framework structure, with three-dimensional open ion channels and a high sodium ion diffusion coefficient (10). -11 cm 2 (on the order of / s), but with low intrinsic electronic conductivity. NFPP is a polyanionic material with a stable crystal framework and a moderate operating voltage (~3.2V vs. Na). + / Na), but the theoretical capacity is relatively low (releasing one Na). +(128mAh / g). The synthesis conditions for both are similar (non-oxidizing atmosphere, 500~750℃), and in-situ recombination is easily achieved by constructing a heterostructure to optimize the electron / ion transport pathway. The high ion diffusion capability of NVP can compensate for the kinetic limitations of NFPP, while the structural stability of NFPP helps to suppress the volume deformation of NVP during charge and discharge (approximately 13.48%).
[0070] Another advantage is capacity matching: NVP has a theoretical capacity of 117.6 mAh / g, while NFPP has a capacity of ~128 mAh / g. Their similar capacity ranges facilitate uniform reaction of the electrode materials. Furthermore, their voltage plateaus are complementary: NVP has a redox potential of ~3.4V (corresponding to V... 3+ / V 4+ ), NFPP is ~3.2V (Fe 2+ / Fe 3+ The composite material can broaden the voltage window and improve the overall energy density. Enhanced cycle stability: The rigid PO4-P2O7 framework of NFPP can buffer the lattice stress of NVP during sodium insertion / extraction, reducing crack formation. Synergistic sodium storage mechanism: The composite system may induce the formation of an intermediate phase (such as Na2V2(PO4)3) at the interface. This phase has a lower sodium ion migration barrier (<0.5 eV) at the NVP-NFPP interface, promoting rapid phase transition reactions. In-situ XRD characterization showed that no two-phase separation phenomenon of pure NVP was observed during the charge-discharge process of the composite material, indicating that the introduction of NFPP can suppress irreversible phase transitions.
[0071] In summary, the composite system of NVP and NFPP demonstrates promising application prospects in high-performance sodium-ion battery cathode materials through structural synergy, kinetic optimization, and resource complementarity. More importantly, it possesses a NASICON (sodium fast ion conductor) structure, exhibiting high ionic conductivity. Therefore, this invention combines NVP and NFPP, ensuring that the NASICON structure of NVP can provide high ionic conductivity for sodium-ion batteries. + It provides a fast transport channel, and the active interface layer between the two phases is also for Na. + Providing more transport channels can significantly improve the ionic conductivity of the material. Secondly, in-situ composite formation of the two phases may result in mutual doping. Studies have shown that bulk doping generally improves the electronic conductivity of electrode materials; therefore, mutual doping of NVP and NFPP is expected to significantly improve the electronic conductivity of the composite material. It should be noted that since the theoretical capacity of NVP is lower than that of NFPP, and V is more expensive than Fe, its doping amount should be minimized while ensuring the modification effect.
[0072] This invention employs a combination of sand milling and spray drying technology to prepare NFPP / C-NVP / C hollow porous spherical composite nanoparticles. By achieving in-situ two-phase composite and in-situ carbon nano-coating, the electrochemical performance of the material is significantly improved. This is a novel and effective modification method with the following advantages: in-situ carbon nano-coating inhibits the growth of active material grains and prevents their aggregation. Furthermore, it inhibits the detachment of active material from the current collector due to repeated volume expansion / contraction during charge / discharge, thus improving its cycle performance. Its electrochemical performance is significantly superior to that of solid or dense electrode materials. The following beneficial effects can be achieved: (1) The synthesis conditions are similar (non-oxidizing atmosphere, 500~750℃), making in-situ composite easy; the two can optimize the electron / ion transport path by constructing a heterogeneous interface; (2) The composite system may form an intermediate phase (such as Na2V2(PO4)3) through interface induction. This phase has a lower sodium ion migration barrier (<0.5eV) at the NVP-NFPP interface, promoting rapid phase transition reaction and suppressing irreversible phase transition; (3) Potential for large-scale application. Both are polyanionic materials with strong compatibility in synthesis processes (such as solid-state method and spray method), and the raw material cost is significantly lower than that of layered oxides. The combination of the iron-based properties of NFPP and the vanadium-based properties of NVP can avoid the problem of dependence on single transition metal resources, which is in line with the low-cost development route of sodium electricity.
[0073] Solid-state synthesis of NVP / C materials typically involves high temperatures (usually above 800°C). Due to the high temperature and long calcination time, the materials tend to have large, uneven particles. Furthermore, the high temperature is detrimental to controlling production energy consumption and equipment maintenance. This invention utilizes a highly reducing organic compound as both a reducing agent and a carbon source to pre-reduce vanadium (V) during mechanical activation. This reduces the calcination temperature and time, resulting in higher-performance NVP / C cathode materials while minimizing energy consumption.
[0074] NFPP is a polyanionic compound with a stable structure and high theoretical specific capacity. Doping primarily enhances performance through the following methods: improving electronic conductivity and reducing internal resistance by doping with high-valence metal ions (such as V) or carbon coating, thereby increasing electronic conductivity; and doping with ions (such as Fe)... 3+ This can stabilize the crystal structure, reduce volume changes during charging and discharging, and improve cycle stability, thereby enhancing structural stability; by doping with ions (such as K+) + Ca 2+ It can increase the lattice spacing, accelerate sodium ion diffusion, improve rate performance, and thus optimize sodium ion diffusion.
[0075] This invention improves conductivity and structural stability through doping and surface coating (such as carbon coating), reduces particle size to shorten ion diffusion paths and enhances reaction kinetics, and reduces side reactions and improves cycle stability by selecting suitable electrolytes and additives, thereby improving the specific capacity, cycle stability and rate performance of the material.
[0076] This invention provides more Na by optimizing the crystal structure. + Diffusion channels, by introducing appropriate defects, increase active sites and promote ion migration. They also improve the interface between the electrode and the electrolyte, reducing interfacial impedance and thus enhancing Na+ absorption capacity. + The diffusion rate in the material.
[0077] This invention selects materials with a stable framework, such as NVP / C materials with a NASICON structure, and reduces volume changes during charging and discharging through material design and preparation processes to construct composite materials. It utilizes the synergistic effect of different components to enhance stability, thereby achieving structural stability of the material under high-rate charging and discharging.
[0078] The modification mechanism of the preparation method of the present invention is as follows: 1. Carbon coating: inhibits grain growth and agglomeration, improves electronic conductivity, and buffers volume expansion.
[0079] 2. Two-phase composite: NVP provides three-dimensional Na + The fast channel and NFPP provide a stable framework, while the heterogeneous interface reduces the barrier to ion migration.
[0080] 3. Mutual doping: Optimizes crystal structure, improves electronic and ionic conductivity, and suppresses irreversible phase transitions.
[0081] 4. Spherical hollow structure: shortens the ion diffusion path, provides sodium storage space, and improves rate capability and cycle performance.
[0082] This invention improves the electronic conductivity and reduces electrode polarization by synergistically enhancing in-situ carbon coating and NFPP / C and NVP / C two-phase doping.
[0083] This invention accelerates Na2O production through the NASICON structure and heterogeneous interface. + This improves transmission and rate performance, thereby optimizing material dynamics.
[0084] This invention uses a rigid polyanionic framework and a hollow structure to buffer volume changes, thereby extending cycle life and stabilizing the material's structure.
[0085] This invention broadens the voltage window through voltage platform complementarity and improves the overall energy density through capacity matching, thereby forming complementary material properties.
[0086] The present invention has advantages in process, including simple process, low synthesis temperature, low energy consumption, and easy scalability.
[0087] The present invention utilizes abundant iron-based resources, and reduces the amount of vanadium used while ensuring performance, thereby lowering material costs and making costs controllable.
[0088] The present invention also provides NFPP / C-NVP / C hollow porous spherical composite nanoparticles prepared by the above preparation method.
[0089] This invention also provides the application of the NFPP / C-NVP / C hollow porous spherical composite nanoparticles prepared by the above preparation method in the preparation of cathode materials for sodium-ion batteries.
[0090] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing NFPP / C-NVP / C hollow porous spherical composite nanoparticles, characterized in that, Includes the following steps: Step 1: Prepare NFPP / C hollow porous spherical nanoparticle precursors; First, sodium source, iron source, and phosphorus source are placed in a solvent in proportion, and carbon source is added. The mixture is stirred until a transparent and uniform first mixed slurry is formed. Then, the first mixed slurry is sand-milled and spray-dried to obtain a dried NFPP / C hollow porous spherical nanoparticle precursor. Step 2: Prepare NVP / C hollow porous spherical nanoparticle precursors; First, sodium source, vanadium source, and phosphorus source are placed in a solvent in proportion, and phosphate chelating agent and carbon source are added. The mixture is stirred until a transparent and uniform second mixed slurry is formed. Then, the second mixed slurry is sand-milled and spray-dried to obtain a dried NVP / C hollow porous spherical nanoparticle precursor. Step 3: Prepare NFPP / C-NVP / C hollow porous spherical composite nanoparticles; The NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed in a certain mass ratio and then calcined in a non-oxidizing atmosphere for a certain time to finally obtain two composites with carbon-coated NFPP hollow porous spherical nanoparticles and NVP hollow porous spherical nanoparticles, namely NFPP / C-NVP / C hollow porous spherical composite nanoparticles.
2. The preparation method according to claim 1, characterized in that, In step 1, the molar ratio of the sodium source, the iron source, and the phosphorus source is Na:Fe:P = 4:3:4, wherein the sodium source is introduced through sodium acetate trihydrate, the iron source is introduced through ferric phosphate, and the phosphorus source is introduced through one of ferric phosphate and ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid.
3. The preparation method according to claim 1, characterized in that, In step 2, the molar ratio of the sodium source, the vanadium source, and the phosphorus source is Na:V:P=3:2:3, wherein the sodium source is introduced by sodium dihydrogen phosphate dihydrate, the vanadium source is introduced by ammonium metavanadate, the phosphorus source is introduced by sodium dihydrogen phosphate dihydrate, and the phosphoric acid chelating agent is one of oxalic acid and citric acid.
4. The preparation method according to claim 1, characterized in that, In steps 1 and 2, the carbon source is introduced through one of sucrose, soluble starch, cellulose, glucose, ascorbic acid, and citric acid; the total amount of the carbon source added is 1 to 10% of the total mass of the sodium source, the iron source, the phosphorus source, and the vanadium source.
5. The preparation method according to claim 1, characterized in that, In steps 1 and 2, the solvent is one of ethanol, acetic acid, or deionized water.
6. The preparation method according to claim 1, characterized in that, In steps 1 and 2, the sanding method is as follows: First, pour the first mixed slurry and the second mixed slurry into their respective sand mills and stir for 1-2 hours; The mixture is then subjected to coarse and fine grinding for 3 to 10 hours to ensure that the particle size of the raw materials in the first and second mixed slurries is uniformly controlled between 0.4 ± 0.1 μm.
7. The preparation method according to claim 1, characterized in that, In steps 1 and 2, the spraying method is as follows: The first and second mixed slurries, after sand milling, are fed to corresponding spray dryers at a feeding rate of 200 mL / h. The inlet temperature of the spray dryer is 200°C and the outlet temperature is 100°C, thereby obtaining the dried NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor, respectively.
8. The preparation method according to claim 1, characterized in that, In step 3, the calcination method is as follows: First, the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed at a mass ratio of 5:5, 6:4 or 7:3, and placed in a tube furnace. Under the atmosphere of argon or argon-hydrogen mixed gas, the mixture is pre-calcined at 300~400℃ for 1~4h at a heating rate of 2℃ / min, and then calcined at 500~750℃ for 5~15h. During the calcination process, the sodium source, the iron source, and the phosphorus source in the NFPP / C hollow porous spherical nanoparticle precursor react to generate Na4Fe3(PO4)2P2O7+NH3, which is the composite sodium iron pyrophosphate NFPP; the sodium source, the vanadium source, the phosphorus source, and the phosphate chelating agent in the NVP / C hollow porous spherical nanoparticle precursor react to generate Na3V2(PO4)3, which is the sodium vanadium phosphate NVP; Meanwhile, the carbon source in the NFPP / C hollow porous spherical nanoparticle precursor and the carbon source in the NVP / C hollow porous spherical nanoparticle precursor can first act as reducing agents to ensure that the elements in the NFPP / C hollow porous spherical nanoparticle precursor and the NVP / C hollow porous spherical nanoparticle precursor are mixed evenly, and after calcination, a dense and uniform conductive carbon layer is formed on the surface of NFPP and NVP respectively, thereby greatly improving the performance of the electrode material; Ultimately, hollow porous spherical nanoparticles are formed by in-situ composite of two phases, NFPP / C and NVP / C, and in-situ carbon coating, namely NFPP / C-NVP / C hollow porous spherical composite nanoparticles, in which NFPP / C is a mixed polyanionic phase of orthorhombic crystal system, and NVP / C is a trigonal NASICON phase.
9. An NFPP / C-NVP / C hollow porous spherical composite nanoparticle prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the NFPP / C-NVP / C hollow porous spherical composite nanoparticles as described in claim 9 in the preparation of cathode materials for sodium-ion batteries.